Interoperability in Project-Based Industries: Learnings and Challenges - Yilmaz, Gokce; Martinsuo, Miia; Gaspar, Henrique; Bronson, Janica (United Kingdom, 2026)
The paper reviews the ongoing issue of interoperability at an organizational level and its importance in the context of Industry 5.0, focusing on the building and maritime industries. The paper explores the potential for cross-industry learning between the two industries, highlighting data domains that can improve project flow while analyzing lessons learned and challenges in the adoption of modern tools for data sharing and management. Findings suggest that establishing clear legal frameworks, adaptable work processes, and cultural dynamics are necessary for improving interoperability. Furthermore, the paper supports a holistic approach that considers human, organizational, and legal dimensions, highlighting guidelines from the European Interoperability Framework (EIF) to improve collaboration across these industries.
11th IFAC Conference on Manufacturing Modelling, Management and Control MIM 2025